Biotechnological transformation of artemisinin: toward an effective antim-malaria drug - Omar, Muhammad Nor; M. Hasali, Nor Hazwani; T. Khan , Naik; Moin, Syed Faraz; Y. AlFarra, Helmi (Oriental Scientific Publishing Co., 2012)
In recent years, artemisinin (1) has remained an effective drug to treat malaria. Numerous approaches have been adapted to increase the efficacy of (1) against antibiotic resistant malarial parasite. Microbial biotransformation of (1) has been used recently to produce promising derivatives of (1) on a large scale with low costs. During the last decade several biotransformation studies on (1), by using microorganisms, have been reported. This literature review focuses on the most recent microbial transformation studies on artemisinin and its derivatives.